2006
DOI: 10.1186/1471-227x-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Errors in fracture diagnoses in the emergency department – characteristics of patients and diurnal variation

Abstract: Background: Evaluation of the circumstances related to errors in diagnosis of fractures at an Emergency Department may suggest ways to reduce the incidence of such errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 8 publications
3
62
2
1
Order By: Relevance
“…Previous studies considering the accuracy of radiograph interpretations by ED staff have often used the radiological interpretafion as the reference (gold) standard [18,23,29] despite sensitivity and specificity being variable and dependent on the imaging examinafion and experience of the reporting radiographer or radiologist [30,31]. In this study, a compound reference standard was applied equally in both arms and concordant interpretafions between ED and radiology staff were assumed to be correct.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies considering the accuracy of radiograph interpretations by ED staff have often used the radiological interpretafion as the reference (gold) standard [18,23,29] despite sensitivity and specificity being variable and dependent on the imaging examinafion and experience of the reporting radiographer or radiologist [30,31]. In this study, a compound reference standard was applied equally in both arms and concordant interpretafions between ED and radiology staff were assumed to be correct.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnostic error is broadly defined as any mistake or failure in the diagnostic process leading to a misdiagnosis, a missed diagnosis or a delayed diagnosis. Failure to diagnose a fracture accounts for up to 80% of ED diagnostic errors, occurs in 1% of all ED visits in a Norwegian hospital (when 3% of fractures were missed) and is a leading cause of litigation . The rate of missed fractures in emergency radiology is highest in the extremities (foot, 7.6%; hand, 5.4%; wrist, 4.1%; ankle, 2.8%), the knee (6.3%), elbow (6.0%) and hip (3.9%) …”
Section: Competing Interestsmentioning
confidence: 99%
“…Guly suggested that fractures might be missed because incorrect radiographs were requested, highlighting the need for a thorough assessment and the need for ED doctors to specify the exact radiographic views that they require, and/or to state exactly the injury that they want to exclude. A lack of cooperation and communication between emergency and radiology departments is also a contributing factor to missed fractures . Additionally, it has been suggested that radiology trainees should have specific training in the interpretation of radiographs, and work under supervision before being allowed to interpret radiographs unsupervised .…”
Section: Competing Interestsmentioning
confidence: 99%
“…[1][2][3][4] Misdiagnosis of a fracture is a very common occurrence in EDs and can have serious consequences because of delays in treatment and resulting long-term disability. [1] It is also one of the most common causes of medical legal claims in the United States. [5,6] Analysis of the circumstances in which errors in medical practice occur may suggest ways to prevent them.…”
Section: Sonuçmentioning
confidence: 99%